2000
DOI: 10.1021/ic990760e
|View full text |Cite
|
Sign up to set email alerts
|

Bonding, Structure, and Energetics of Gaseous E82+and of Solid E8(AsF6)2(E = S, Se)

Abstract: The attempt to prepare hitherto unknown homopolyatomic cations of sulfur by the reaction of elemental sulfur with blue S8(AsF6)2 in liquid SO2/SO2ClF, led to red (in transmitted light) crystals identified crystallographically as S8(AsF6)2. The X-ray structure of this salt was redetermined with improved resolution and corrected for librational motion: monoclinic, space group P2(1)/c (No. 14), Z = 8, a = 14.986(2) A, b = 13.396(2) A, c = 16.351(2) A, beta = 108.12(1) degrees. The gas phase structures of E8(2+) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 80 publications
5
95
0
6
Order By: Relevance
“…This is due to the strong electrostatic repulsion of the two adjacent positive charges in À assuming ionic radii are similar, as shown by the Kapustiniskii equation (Fig. 6a) 41,[59][60][61] , where z x and z y are the charge of the ions, r x and r y the ionic radii and n is the number of ions per formula unit (for example, two for X þ Y À and three for X 2 þ (Y À ) 2 ). As shown in the Born-Fajans-Haber cycle (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…This is due to the strong electrostatic repulsion of the two adjacent positive charges in À assuming ionic radii are similar, as shown by the Kapustiniskii equation (Fig. 6a) 41,[59][60][61] , where z x and z y are the charge of the ions, r x and r y the ionic radii and n is the number of ions per formula unit (for example, two for X þ Y À and three for X 2 þ (Y À ) 2 ). As shown in the Born-Fajans-Haber cycle (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…7,8 For S8 2+ , the high-resolution X-ray structure of the salt S8(AsF6)2 by Passmore et al is used as a reference, 19 while the optimized metrical parameters of Se8 2+ are compared with data for the dication in the salt (Te6 4+ )(Se8 2+ )(AsF6 -)6(SO2) as determined by Gillespie et al 17 In the crystallographic data, tetrachalcogen tetranitrides and octachalcogen dications have nearly ideal D2d and Cs molecular symmetries, respectively. 4,5,7,8,15,19 For E4N4, there are several short (3.1 -3.2 Å) E⋯N contacts between the four molecules in the unit cell. Similarly, short (2.7 -3.3 Å) E⋯F contacts exist between the chalcogen dications and AsF6 -anions in the X-ray data of both S8 2+ and Se8 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…were subjected to Natural Bond Orbital (NBO), Atoms in Molecules (AIM) and An AIM analysis of the total electron densities of E8 2+ dications has previously been conducted by Passmore et al 19 The acquired data shows that a bond critical point is indeed found for the transannular E⋯E interaction and it is characterized by small values of both the electron density  (0.04 a.u. for S8 2+ ) and its Laplacian  2 (0.…”
Section: Geometry Optimizations Using a Cas-type Wave Function Yield mentioning
confidence: 99%
See 1 more Smart Citation
“…A colorless crystal of S 4 (AsF 6 ) 2 ¢AsF 3 was analyzed by X-ray crystallography. 33 The diamagnetic S 4 2+ possesses a square-planar structure (SS bond (¡): 1.999(4), 1.946(4), 1.924(4), and 1.986(4), SSS bond angle (deg): 91.7(2), 91.5(2), 87.9(2), and 88.9(2)), with a quasiaromatic 6³ four-membered ring. In the early stage of theoretical study of S 4 2+ , Fukui et al performed calculation of its electronic state using semiemprical INDO method for valence electrons and assigned the weak absorption band at 280 nm to the 2e u ¼ 3e u transition which is forbidden by symmetry.…”
Section: ç Rectangular S 4 Species In Metal Complexesmentioning
confidence: 99%